“Cuidados de enfermería en pielonefritis crónica en un paciente con lupus eritematoso sistémico” - Zamora Castillo, María José (2024)
Chronic pyelonephritis is among the leading causes of chronic renal failure and arterial hypertension, imposing a significant burden on health. Moreover, in patients with systemic lupus erythematosus it may present with atypical or aggravated symptomatology due to the presence of systemic inflammation and immune dysfunction typical of this autoimmune disease. For this reason, the aim of this study was to implement nursing care in chronic pyelonephritis in a patient with systemic lupus erythematosus, considering its clinical particularities and individual characteristics for specialized care through the nursing care process. The method used to achieve the aforementioned was through a thorough assessment of the clinical history and by means of Marjory Gordon's functional patterns, among which the elimination, activity-exercise and cognitive-perceptual patterns were found to be altered. Then, nursing care plans focused on the improvement of pain control, urinary function and endurance were proposed, interpreted in the selection of nursing diagnoses, as well as acute pain, altered urinary elimination and decreased tolerance to activity. Finally, it is concluded that the interventions implemented achieved the expected results, reaching an optimal evolution in the condition of the patient under study.